Praeksistensi, Inkarnasi, dan Pemuliaan Kristus: Studi Kristologi Filipi 2:1–11: Studi Kristologi Filipi 2:1-11 - Diana Waruwu; Agustinus Djoko Susanto (STAK Reformed Remnant Internasional, 2026)
This article examines Philippians 2:1–11 as a unified Christological teaching that encompasses the preexistence, incarnation, and exaltation of Christ. The study addresses a research gap in interpretations that tend to separate the ethical and dogmatic dimensions of the passage, resulting in a partial reading. This research employs a qualitative library-based approach through exegetical and theological analysis of Philippians 2:1–11, combined with engagement with Western and Indonesian theological literature. The discussion focuses on Christ’s preexistence as divine existence prior to the incarnation, the incarnation of Christ through kenosis expressed in obedience unto death on the cross, and the exaltation of Christ as God’s act of exalting Him and granting the name above every name. The findings demonstrate that these three aspects form an interconnected sequence of salvific work and constitute a foundational element of Pauline Christology. This study affirms that Philippians 2:1 – 11 is not merely an ethical exhortation but a doctrinal foundation that remains relevant for theological reflection and the life of the church today.